Patient and disease characteristics associated with late tumour stage at presentation of cervical cancer in northwestern Tanzania. Issue 1 (December 2015) - Mlange, Ramadhani; Matovelo, Dismas; Rambau, Peter; Kidenya, Benson
Abstract Background About two thirds of patients with cervical cancer in Tanzania present with advanced tumor stage, leading to significant morbidity and mortality. We designed a study to determine the factors associated with the late tumour stage at presentation among patients with cervical cancer in Mwanza. Methods This cross-sectional study recruited women at Bugando Medical Centre (BMC) with histologically confirmed cervical cancer from November 2013 to April 2014. Patients were recruited serially until the sample size was reached. Results A total of 202 women with histologically confirmed cervical cancer were recruited. The mean age of the patients was 50.5 ± 13.3 years. The majority of patients (n = 129, 63.9 %) were diagnosed with late stage disease (IIB-IVB). Patients also presented with severe anemia (n = 78, 38.6 %), urinary tract infections (n = 74, 36.6 %), hydronephrosis (n = 43, 21.2 %), elevated serum creatinine levels (n = 33, 16.3 %), vesicovaginal fistula (VVF), (n = 13, 6.4 %), lung metastasis (n = 5, 2.4 %), metastasis to the urinary bladder (n = 4, 1.9 %), rectovaginal fistula (RVF) (n = 3, 1.4 %), liver metastasis (n = 2, 0.9 %) and hydroureter (n = 2, 0.9 %). In multivariate logistic regression, factors associated with late stage at presentation were attending to alternative health practitioners and lack of personal initiative to seek care to formal health facilities (OR 2.3; 95 % CI 1.2–4.2, p = 0.011 and OR 2.0; 95 % CI 1.0–3.8, p = 0.028) respectively. Conclusion Communities should be sensitized to women's empowerment, provide community education on early symptoms of cervical cancer, and the importance of early hospital attendance.